PERTANGGUNGJAWABAN PIDANA ORANG TUA YANG MELAKUKAN EKSPLOITASI ANAK - Hidayatullah, Maulana Syarif; Nugroho, Widhi Cahyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Children are the nation's next generation who should be protected by various parties starting from the smallest environment, namely the family, society, government and the state. The responsibility of parents who exploit children and how to handle those carried out by parents and children who become victims. Crimes committed against children as victims often occur but society does not respond to these crimes so that in the end these crimes are considered reasonable, especially if they are committed by parents of the child. The crime that is often committed by parents against their biological children is deliberately neglecting the method used in this research, which is a type of empirical legal research that aims to find out how far the law works in society. primary and secondary needs of the child. Basically neglect of children is included in social violence which causes psychological and physical injuries and of course it is very imprinted in the memory of children who are victims of this neglect. Neglect of these children is a prelude to exploitation with the modus operandi of making biological children as beggars and buskers in order to meet the needs of family life which should not be the responsibility of a child in the family. Actors who make children as beggars and buskers are the smallest unit in society, namely people Old. Criminal liability for people who intentionally exploit children economically with the modus operandi of making these children become beggars and buskers is regulated in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection